Fight or flight: managing stigma in executive careers - Semadeni, Matthew; Cannella Jr, Albert A.; Fraser, Donald R.; Lee, D. Scott (Strategic management journal, 2008)
We examine the labor market consequences borne by executives who remain at financially distressed firms relative to those who flee to another employer to avoid the stigma of failure. Our study makes two contributions. First, we document an ex ante dimension of executive labor markets unaccounted for by ex post settling up models. Specifically, we show that executives who 'jump ship'--change employers in the two years prior to the failure--suffer fewer labor market consequences than their counterparts who remain with the failing firm. Second, we extend the study of bankruptcy stigma to examine how stigma might be managed by jumping ship.